Aegean Frescoes and Their Correlating Myths - Dugan, Shannon Shields (East Carolina University, 2023)
The interpretation of frescoes at an archaeological site can provide significant information on the function of the room in which they’re located, as well as provide insight into the past culture and its relation to other successive cultures. Through two case studies, Dr. Mazow and I compared written and visual expressions of Greek myths to scenes painted on the walls at two different Bronze Age Aegean sites. Based on our research we have found strong parallels between these frescoes and their depictions in later Greek myths. In the first example, we suggest the two women facing each other reflects the myth of the weaving contest between Athena and Arachne. For the second example, we suggest it depicts the story of Demeter and the descent of Persephone. Showing that these myths may have an earlier visual expression that predates their written record provides insight into how images were used in communication, a connection between Bronze age cultures and Classical Antiquity, and further enhances our identification of room and building function.
Keywords: Greek mythology, archaeology, anthropology, Bronze Age, frescoes